PENGARUH DANA PIHAK KETIGA (DPK) DAN CAPITAL ADEQUACY RATIO (CAR) TERHADAP PENYALURAN KREDIT UMKM PT BANK CENTRAL ASIA Tbk - Nurfajri, Nisa Rajabi; Mirati, R. Elly (Yayasan Education and Social Center, 2024)
The objective of this study is to examine the impact of Capital Adequacy Ratio (CAR) and Third Party Funds (DPK) on MSME credit distribution at PT Bank Central Asia Tbk. between 2019 and 2023. The time series data utilized in this study is secondary data that was taken from Bank BCA's published quarterly financial reports for the 2019–2023 fiscal year. Multiple linear regression analysis is the analysis method utilized to ascertain the relationship between the variables. The study's findings suggest that, at least in part, the Capital Adequacy Ratio (CAR) and Third Party Funds (DPK) have a considerable favorable impact on the MSME loan distribution at PT Bank Central Asia Tbk. between 2019 and 2023. From 2019 to 2023, the Capital Adequacy Ratio (CAR) and Third Party Funds (DPK) have a major impact of 77.7% on the MSME loan distribution at PT Bank Central Asia Tbk. Other variables affect the remaining 22.3% of the credit distribution